Potensi Dan Hambatan Objek Wisata Di Kecamatan Sumpur Kudus Kabupaten Sijunjung - Dela, Dela; Bakarudin, Bakarudin; Yuherman, Yuherman (STKIP PGRI Sumbar, 2013)
This research intent describes to hit region that potentially to at makes as wisatas place at Sumpurs district Sijunjungs Regency holy. This observational type is descriptive kualitatif. Data source that is taken is word and indigenous action peopled one knows about problem observational subjek this research is Nagaris Guardian Peripheral, Society and Young Men opener. Subjek is research which is with data collecting tech that doing to pass through interview, observation, and photography. data analyst tech that is done is data reduction, data representation, and gleaning from. Tech tests data authenticity, data and participation representation, observer and triangulation persistence. menunjukans observational result (1 ) regions that potentially as wisatas place which is (a ) kenagarian Sumpur potency holy that at has it which is Panorama Bukik Lantiak, Lubuak Pandakians waterfall, and Syehk Ibrahims Sepulchre (b ) kenagarian Silantai potencies that at has which is as PDRIS Monument, and Rimbo Lisun (2 ) aught interference which is Sumpurs region transportation off-centered enough holies districts so needs long time enough times at tripping it even theres only one workaday car in out region with circumscribed time too, Farm release whereabouts farm which will at open goes to regions that potentially its field is so difficult, and negative Myth Influence.